The Depiction of the Meaning of Death through Iola and Anest Character in Salt Root and Roe - Puspita, Yulia Mega (CV. Era Digital Nusantara, 2023)
Death has meaning for each individual, which sometimes holds meaning about the psychological soul in literature. Anxiety, fear of abandonment, and betrayal become unconscious individual factors. These factors are not only conveyed in physical and emotional form but also in the written form of literary works such as contemporary drama. This study discusses how the meaning of death is tied to anxiety, fear of abandonment, and betrayal in a play entitled Salt Root and Roe by Tim Price. This literary work shows how the deaths of the main characters, namely Iola and Anest, twin sisters, are linked to incidents of anxiety and fear originating from childhood trauma, so this influences their subconscious decisions. To analyze and answer the study objectives, the author used qualitative research methods with Sigmund Freud's psychoanalytic theory approach. This study analyzes from the perspective of Freud's psychoanalysis using the tripartite theory of id, ego, and superego of the characters Iola and Anest to discover the character's desires and decisions influenced by their environment. In the process of this analysis, it was discovered that the twin characters, Iola and Anest, had trauma in their childhood, which resulted in anxiety, betrayal, and fear of being abandoned by each other or being abandoned by their loved ones due to the influence of an environment and family that was less than supportive during their childhood. In addition, this study found that Iola and Anest's meaning of death tied each other to each other, indicating that their relationship did not want to be abandoned again and experienced the trauma and disappointment of being abandoned in the past. Tragic death in this literary work means a togetherness created by the characters' deep-seated fears, traumas, and betrayals.